Emerging Roles on Immunological Effect of Indoleamine 2,3-Dioxygenase in Liver Injuries - Xu, Lingyan; Ling, Jiawei; Su, Chang; Su, Yu-Wen; Xu, Yan; Jiang, Zhenzhou (Frontiers in Medicine, 2021)
Indoleamine 2,3-dioxygenase (IDO) is one of the initial rate-limiting enzymes of the kynurenine pathway (KP), which causes immune suppression and induction of T cell anergy. It is associated with the imbalance of immune homeostasis in numerous diseases including cancer, chronic viral infection, allergy, and autoimmune diseases. Recently, IDO has extended its role to liver field. In this review, we summarize the dysregulation and potentials of IDO in the emerging field of liver injuries, as well as current challenges for IDO targets. In particular, we discuss unexpected conclusions against previous work published. IDO is induced by pro-inflammatory cytokines in liver dysfunction and exerts an immunosuppressive effect, whereas the improvement of liver injury may require consideration of multiple factors besides IDO.